2007
DOI: 10.1002/glia.20613
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural plasticity in the rat suprachiasmatic nucleus. Possible involvement in clock entrainment

Abstract: Circadian rhythms in mammals are synchronized to the light (L)/dark (D) cycle through messages relaying in the master clock, the suprachiasmatic nucleus of the hypothalamus (SCN). Here, we provide evidence that the SCN undergoes rhythmic ultrastructural rearrangements over the 24-h cycle characterized by day/night changes of the glial, axon terminal, and/or somato-dendritic coverage of neurons expressing arginine vasopressin (AVP) or vasoactive intestinal peptide (VIP), the two main sources of SCN efferents. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 44 publications
5
103
1
4
Order By: Relevance
“…Ultrastructure analyses combined with other methods helped to demonstrate rapid and reversible structural remodeling of astrocytic processes in the hypothalamus (Becquet et al, 2008; Theodosis et al, 1981). These changes follow several types of stimulation, including lactation, parturition, and stress (Montagnese et al, 1988; Oliet et al, 2001; Salm, 2000; Theodosis, 2002).…”
Section: Current Methods To Monitor Fine Astrocyte Morphology: Promismentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrastructure analyses combined with other methods helped to demonstrate rapid and reversible structural remodeling of astrocytic processes in the hypothalamus (Becquet et al, 2008; Theodosis et al, 1981). These changes follow several types of stimulation, including lactation, parturition, and stress (Montagnese et al, 1988; Oliet et al, 2001; Salm, 2000; Theodosis, 2002).…”
Section: Current Methods To Monitor Fine Astrocyte Morphology: Promismentioning
confidence: 99%
“…Additionally, in such cases, less d ‐serine may be available from astrocytes for the co‐agonist activation of postsynaptic NMDARs and thus the machinery of long‐term synaptic plasticity in the SON (Panatier et al, 2006). In the same area of the hypothalamus glial coverage of neurons also follows a circadian rhythm with changes of dendritic enwrapping during day and night (Becquet et al, 2008). …”
Section: Implications Of Pap Morphogenesis For Synaptic Functionmentioning
confidence: 99%
“…If this is the case, then it is possible that the retraction of astrocytic processes disrupts this relationship and that the spatial mismatch between taurine release and GlyRs prevents their activation because of the effect of distributed taurine uptake on bulk extracellular taurine levels. Interestingly, morphological astrocyte plasticity has been shown to occur in other parts of the brain [e.g., suprachiasmatic nucleus (Becquet et al, 2008), brain stem (Hirrlinger et al, 2004), and cortex (Jones et al, 1996)], and recent imaging studies have shown that astrocytic processes are highly motile and capable of extending and retracting on a time scale of minutes (Haber et al, 2006). Therefore, it is possible that taurinergic gliotransmission is a process that can be regulated dynamically in response to changes in astrocyte morphology.…”
Section: Possible Role Of Taurinergic Gliotransmission In Other Brainmentioning
confidence: 99%
“…Glucocorticoid signaling has been shown to reset circadian timing in peripheral tissues, thus transmitting the time cues originating from the SCN (Balsalobre et al 2000). In addition, although the SCN does not express glucocorticoid receptors, indirect feedback signals might reach the central oscillators, since glucocorticoid rhythms have been described to influence photic entrainment, as well as rhythms in the expression of the glial-specific protein GFAP in the SCN (Becquet et al 2008;Kiessling et al 2010;Sage et al 2004). The SCN can also communicate timing signals to peripheral tissues through the autonomic nervous system.…”
Section: Entrainment Of Peripheral Oscillatorsmentioning
confidence: 99%